Disorientation: An Introduction - Martin, Niall; Rosello, Mireille (Culture, theory and critique, 2016)
This collection of essays analyses the concept of disorientation. It does so by questioning orientation as norm and disorientation as resistance. This exploration of disorientation does not interpret the disoriented subject as the privileged site of new knowledge, dissident pleasure or social critique. Nor does it propose to embrace disorientation as the invisible norm revealed by the study of supposedly exceptional subjects. Contemplating the concept of disorientation does not mean becoming disoriented, nor does it mean adopting a position of condescending mastery or blind admiration vis-à-vis the disoriented other. We argue that only when it becomes possible to imagine, simultaneously, many incompatible or at least discrepant possible forms of powerful, powerless, desirable and undesirable forms of disorientation, does disorientation become a political tool. We can then imagine disorientation as the name of the constantly evolving relationality between a subject and a conscious or unconscious cultural and political grid. Disorientation is the moment during which a world is produced by the acknowledgment of its dependency on the grid. It is also the moment when some subjects are enabled or disenabled by their relationship to the grid and the world in the absence of others who function as the guardians of the norm. What matters here is the subject's positioning vis-à-vis his or her awareness of dis-re-orientation. The question is not who is lost or who is foreign, who is comfortable or who has colonised, who decides where maps stop and start, but rather what kind of relationality explains who feels dis- or re-oriented.